Implementasi Akad Pembiayaan Murabahah Perspektif Ekonomi Syariah (Studi Kasus Di Kspps Safana Ahza Yumna Metro Utara) - Asmuni (LPPM Institut Al-Ma'arif Way Kanan, 2021)
Baitul Maal Wat Tamwil is a community business institution that develops aspects of production and investment to improve the quality of economic activities on a small and medium scale. KSPPS Safana Ahza Yumna is a cooperative institution that legally handles the collection of maal funds (wealth) for Islam including zakat, infaq, and shadaqah and also handles financial services (tamwil) which includes savings and financing for productive businesses to its members and customers/general public. One of its financing service products is murabaha financing. Murabaha is an activity of buying and selling at the basic price with an agreed additional profit. The formulation of the problem in this study is how is the implementation of the Murabahah Financing Agreement in the Baitul Maal Wattamwil Savings and Loan Cooperative (BMT) Safana Ahza Yumna Purwosari Metro? The purpose of this study was to determine the implementation of the Murabahah Financing Agreement in the Baitul Maal Wattamwil Savings and Loan Cooperative (BMT) Safana Ahza Yumna Purwosari Metro. This research is a qualitative research with a descriptive approach. The data collection technique is technique, observation, interview and documentation. While the data analysis technique is a descriptive mindset. Based on the results of the study, it was found that the implementation of the murabahah contract at BMT Mentari, namely the financing products issued by BMT Safana Ahza Yumna, were of two types; first, bai bi tsaman ajil (BBA) financing, namely the provision of capital to purchase goods with installment payments with a profit sharing system or installment financing. Second, murabahah financing (deferred payment or at the end of the agreement) or maturity financing. Distribution of funds in the form of murabahah is the sale of goods from BMT to customers, with the price set at the cost of the goods plus the agreed profit margin. In line with the rules set by Sharia Economic Law, BMT Safana Ahza Yumna has implemented the existing provisions regarding the management of the Murabahah contract, so that the Murabahah contract applied at BMT Safana Ahza Yumna Metro Utara does not conflict with Sharia Economic Law